Closed depressions in the loess areas of Poland. Current state of research and prospects for further research: https://doi.org/10.26485/AGL/2017/106/8 - Kołodyńska-Gawrysiak, Renata (Acta Geographica Lodziensia, 2018)
Closed depressions (CDs) are typical geomorphological features of the loess belts in Europe and their origin is highly debated in literature. This paper presents the current state of research on CDs in the loess belts in Poland. A review was conducted of several studies describing CDs. The existing genetic hypothesis and the scope of future research are described. Morphometric features of CDs, distribution and geological conditions were described in several publications so far. In the selected CDs, colluvial sediments and fossil soils were studied. Various processes (primary and secondary): deflation, uneven loess deposition, suffosion, extrusion of strongly saturated layers, thermokarst were reported as probable genetic processes. CDs act as important archives allowing a reconstruction of natural and anthropogenic processes operating in the past. More research is needed for a better understanding of the origin and evolution of CDs. This will help better understand the importance of the Late Glacial and Holocene stages for the morphogenesis of the loess belts in Europe